Pemanfaatan Media Sosial dalam Manajemen Bencana: Studi Kasus Badan Penanggulangan Bencana Daerah (BPBD) Kabupaten Blitar - Kayla Rahima Putri Wijanarko (Fakultas Ilmu Sosial dan Ilmu Politik, 2026)
Blitar Regency is an area with a relatively high level of disaster risk, predominantly characterized by hydrometeorological hazards and accompanied by potential geological threats. These conditions require disaster management efforts that extend beyond emergency response and emphasize mitigation and community preparedness. Along with the advancement of information technology, social media has emerged as a potential instrument to support disaster communication. This study aims to analyze the utilization of social media by the Regional Disaster Management Agency (BPBD) of Blitar Regency in disaster mitigation, examine the policy framework supporting its use, and assess the influence of social media management on community preparedness. This research employs a qualitative descriptive approach, with data collected through interviews, observation, and documentation. The findings indicate that BPBD Blitar Regency has utilized social media as part of its disaster communication system across the pre-disaster, emergency response, and post-disaster phases, primarily for disseminating weather information, early warnings, disaster incident reports, and documentation of disaster management activities. While social media contributes to increasing public awareness and vigilance, its use remains largely informative and one-directional. The absence of specific technical policies, limited human resources, and constraints in budget allocation and technological support constitute the main challenges to optimizing social media utilization. Therefore, social media holds significant potential to be developed as a more participatory and sustainable disaster mitigation instrument through strengthened policies, institutional capacity, and well-directed disaster communication strategies.
Validasi_26 Mei 2026_Yudi_Naomy
Keywords: disaster management; social media; disaster mitigation; policy implementation; BPBD